2020
DOI: 10.1093/cvr/cvaa310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of p66shc and/or cyclophilin D results in decreased pulmonary vascular tone

Abstract: Aims The pulmonary vascular tone and hypoxia-induced alterations of the pulmonary vasculature may be regulated by the mitochondrial membrane permeability transition pore (mPTP) that controls mitochondrial calcium load and apoptosis. We thus investigated, if the mitochondrial proteins p66shc and cyclophilin D (CypD) that regulate mPTP opening affect the pulmonary vascular tone. Methods and Results Mice deficient for p66shc (p6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…However, our data did not indicate differences between WT and p66KO hearts regarding hemodynamic, functional, and morphological parameters suggesting that p66shc deletion per se had no impact on the development of RV hypertrophy and function upon pressure overload. Similarly, our recent work demonstrated that p66shc deletion does not influence cardiac function in hypoxia-induced pulmonary hypertension [54]. Our previous data also exclude a contribution for p66shc in myocardial ischemia/reperfusion injury and the protection from it by ischemic preconditioning, both conditions in which ROS play important roles [55].…”
Section: Discussionsupporting
confidence: 73%
“…However, our data did not indicate differences between WT and p66KO hearts regarding hemodynamic, functional, and morphological parameters suggesting that p66shc deletion per se had no impact on the development of RV hypertrophy and function upon pressure overload. Similarly, our recent work demonstrated that p66shc deletion does not influence cardiac function in hypoxia-induced pulmonary hypertension [54]. Our previous data also exclude a contribution for p66shc in myocardial ischemia/reperfusion injury and the protection from it by ischemic preconditioning, both conditions in which ROS play important roles [55].…”
Section: Discussionsupporting
confidence: 73%
“…Afterwards, the arteries were flushed with PSS until the baseline was reached, and then equilibrated for 30 min in Ca 2+ -free PSS (in mM, NaCl 119, KCl 4.7, MgSO 4 1.17, KH 2 PO 4 1.18, MnCl 2 2.5, EGTA 10, EDTA 0.03, Glucose 5.5, NaHCO 3 25, pH 7.4). The arterial stiffness was assessed as previously described ( Gierhardt et al, 2022 ): The distance between the wires was increased stepwise while recording the corresponding force in mN. Using the DMT normalization feature in Labchart (ADInstruments, Dunedin, New Zealand), the resulting stress-strain curve displaying the relationship between the logarithmically transformed resting wall tension and the corresponding internal diameter was calculated via regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…p66shc, a shc adaptor protein family member, participates in modulating mitochondrial homeostasis, apoptosis, and production of autophagosomes. 124 siRNA-packaged nanoparticles relieve neuropathic pain through decreasing autophagic, mitophagic, and neuroinflammatory processes both in the L5 spinal cord of SNL-evoked neuropathic pain rats and H 2 O 2 -exposed neuronal cells. 125…”
Section: Neuronal Cellsmentioning
confidence: 98%
“…Carvacrol ameliorates these alterations, demonstrating that NLRP3 suppression by carvacrol potentially puts down to autophagic activation through Keap1/Nrf2/p62 and augmented mitochondrial quality control. p66shc, a shc adaptor protein family member, participates in modulating mitochondrial homeostasis, apoptosis, and production of autophagosomes 124 . p66shc siRNA‐packaged nanoparticles relieve neuropathic pain through decreasing autophagic, mitophagic, and neuroinflammatory processes both in the L5 spinal cord of SNL‐evoked neuropathic pain rats and H 2 O 2 ‐exposed neuronal cells 125 …”
Section: Strategies Targeting Stress/cell Death Pathways In Neuropath...mentioning
confidence: 99%